Pengaruh Strategi Pemasaran Digital dan Customer Experience terhadap Minat Beli Konsumen Mitra Baker Old Lambang Sari - Faisal Alparizzi; Asep Dony Suhendra (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
The rapid development of digital technology has significantly transformed marketing strategies, particularly in the micro, small, and medium enterprises (MSMEs) sector, including Mitra Baker Old Lambang Sari, which strives to expand its market reach and enhance competitiveness through the adoption of digital marketing. Digital marketing today functions not only as a promotional tool but also as an interactive medium that shapes customer experience at every stage of the consumer journey. This study aims to analyze the extent to which digital marketing strategies and customer experience contribute to consumer purchase intention for Mitra Baker Old Lambang Sari products. A quantitative research design was applied using a survey method, with questionnaires distributed to 100 respondents. The collected data were analyzed using SPSS version 25 through partial tests, simultaneous tests, and the coefficient of determination. The partial test results revealed that both digital marketing strategies and customer experience individually exert a positive and significant influence on purchase intention, as evidenced by a significance value of 0.000 (< 0.05) and t-values exceeding the critical t-table values. Furthermore, the simultaneous test confirmed that the two variables jointly have a significant effect, supported by an F-value of 108.003, which is greater than the F-table value of 3.09, and a significance level of 0.000. The coefficient of determination (R Square) was 0.690, indicating that 69% of the variation in consumer purchase intention is explained by digital marketing strategies and customer experience, while the remaining 31% is influenced by other factors not examined in this study. These findings highlight that implementing effective digital marketing strategies alongside delivering high-quality customer experiences is crucial for enhancing consumer purchase intention in MSMEs within the digital era.